Predictors of successful natural sleep MRI for sensorineural hearing loss in infants. (February 2023) - Liao, Elizabeth N.; Li, Yi; Fung, Andrea; Lawless, Lindsay; Czechowicz, Josephine; Ho, Melissa; Luu, Kimberly; Meyer, Lauren; Mohamad, Noura I.; Nadaraja, Garani S.; Taketa, Emily; Virbalas, Jordan; et al.
Abstract: Objectives: Cochlear implantation (CI) in children with sensorineural hearing loss (SNHL) before 12 months of age (mo) improves language outcomes. MRI is important to assess CI candidacy. Anesthesia before 3 years old may increase risk of neurocognitive delay. Natural sleep MRI (NS-MRI) is an emerging technique to avoid anesthesia in infants, but relies on successful sleep for adequate imaging. Our multidisciplinary team hypothesized the following predictors of successful NS-MRI for CI evaluation: age, distance travelled, comorbidities, primary language, insurance type, HL characteristics, time and duration of MRI. Methods: We performed retrospective review of children 0–12mo who attempted NS-MRI. The NS-MRI was successful if imaging was sufficient for definitive clinical management per the managing otolaryngologist. Results: Among 26 patients (29 scans), the median age was 3.2mo (range: 1.2–6.8mo), distance travelled was 16.3 miles (range: 0.9 to 365 miles), 12 (46%) children had medical comorbidities. 8 (31%) had public insurance. 10 (38%) had bilateral HL. 52% (15/29) of scans were successful. Patients with comorbidities had significantly lower odds of successful NS-MRI (OR 0.09; 95% CI 0.01–0.54). Success was not associated with age, distance travelled, insurance type, primary language, HL characteristics, time or duration of MRI on univariable analysis. All 11 children who failed NS-MRI underwent hearing-aid fitting and/or imaging with sedation and CI as clinically indicated before 12mo. Conclusion: NS-MRI was successful in 52% of infants, regardless of age, demographics, HL or MRI characteristics. Unsuccessful NS-MRI did not result in delayed intervention. NS-MRI is an effective consideration for a broad range of infants with SNHL.